Weight loss journeys: Exploring social influences and determinants of health in an exploratory rural German intervention - Constanze Betz; Tina Bartelmeß (PLoS ONE, 2025)
Overweight and obesity are highly prevalent across Western populations and contribute substantially to the global burden of non-communicable diseases such as cardiovascular disease and diabetes. Despite numerous intervention efforts, achieving and sustaining long-term weight loss remains a challenge. Social Determinants of Health (SDoH) play a critical role in shaping health outcomes – including weight and weight loss trajectories – and vary across social groups and geographic contexts. This qualitative study explores participants’ perceptions of personal and contextual SDoH influencing their weight loss journeys within a rural German population enrolled in a general practitioner-led pilot intervention. Semi-structured interviews were conducted with 16 participants from the HAPpEN trial (General Practitioner-led Obesity Prevention Program: Exercise and Nutrition), which focused on individuals living in a rural area of Upper Franconia. Interview data were analyzed using a grounded theory-informed approach to qualitative content analysis, guided by the SDoH framework as a sensitizing concept. Coding and theme development followed an iterative process involving constant comparison and discussion within the research team. Key determinants affecting weight loss efforts included individual routines and schedules, social and household networks, mental health, and work-related demands. Broader contextual factors such as socialization, cultural norms, and the availability of health-supporting infrastructure also emerged. The dynamic interplay between personal motivation and structural or environmental influences appeared to be central to weight management success. This study is limited by its small and relatively homogeneous sample – predominantly female and drawn from a single rural region – which may restrict transferability to more diverse populations or urban settings. Nonetheless, the findings offer practical implications for tailoring weight loss interventions to rural contexts by incorporating the complexity of individual and social determinants.